(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: A study of knowledge, attitude and practices of breastfeeding among mothers delivered in tertiary care hospital in central India. Material and methods: Pretested questionnaires were asked to postnatal mothers after delivery of a live birth baby. A face to face interview will be conducted in the post-natal ward. After the data collection procedure, mothers will be instructed about the proper breast feeding techniques and the benefits of feeding. 400 postnatal mothers will be included in the study and those who are not willing to be part of the study, mothers who deliver preterm baby and critically ill mothers will be excluded from the study. Results: Although the majority of moms (90%) were nursing their newborns, just 25% were exclusive breast feeders, and 35% began breastfeeding within an hour after birth. The majority of the mothers agreed that Colostrum is the first breast milk, and may be watery in (92%), consistency but is extremely crucial for the new born (85%), Colostrum is important for the baby to maintain immunity (70%), Exclusive breastfeeding implies giving no other feed to the baby other than breast milk (61%), Exclusive breast milk is completely adequate for newborns (78%), Knows Exclusive breastfeeding is for up to 6 months of age (85%). The average score of the IIFAS (61.25±5.89) lay in the range of ‘neutral breastfeeding attitudes’. Most of the individual items had a mean score over 3 and only three items had a mean score less than 3, indicating that most of the mothers had neutral to positive attitude towards breast feeding. Conclusion: According to the findings of this research, moms had extremely high knowledge and neutral views on breast feeding. Our data also reveal that exclusive breast feeding was uncommon among Indian moms. As a result, it is critical to give prenatal breast feeding information to moms and dads. We also urge that public health education initiatives to encourage breast feeding be strengthened.